2018
DOI: 10.1097/pts.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Safety Culture in Iranian Academic Hospitals: Strengths and Weaknesses

Abstract: The PSC of the investigated hospitals is not at an ideal level and is in need of serious improvement, particularly in the dimensions of feedback and communication regarding errors, communication openness, staffing, and nonpunitive response to error. The same conditions hold true for other Iranian hospitals (i.e., the Afshar and Sadoughi hospitals in the city of Yazd, Iran), and American hospitals were used for comparison purposes in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 11 publications
5
18
0
7
Order By: Relevance
“…And hence, it may lead to reduction in nurses' error reporting (Behzadifar et al, ). Challenges as to no punitive response to error were also highlighted in a previous study in Iran (Raeissi, Reisi, & Nasiripour, ). In a study carried out in the Netherlands, of 522 “unintended events” at 10 EDs, nurses reported 85% of events and about 83% of the reports were recorded by whom involved in the event (Smits, Groenewegen, Timmermans, van der Wal, & Wagner, ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…And hence, it may lead to reduction in nurses' error reporting (Behzadifar et al, ). Challenges as to no punitive response to error were also highlighted in a previous study in Iran (Raeissi, Reisi, & Nasiripour, ). In a study carried out in the Netherlands, of 522 “unintended events” at 10 EDs, nurses reported 85% of events and about 83% of the reports were recorded by whom involved in the event (Smits, Groenewegen, Timmermans, van der Wal, & Wagner, ).…”
Section: Discussionmentioning
confidence: 63%
“…They measure all the 12 aspects of PSC: “communication openness, feedback and communication about errors, frequency of events reported, handoffs and transitions, management support for patient safety, non‐punitive response to error, organizational learning continuous improvement, overall perceptions of patient safety, staffing, supervisor/manager expectations and actions promoting safety, teamwork across units and teamwork within units.” The scale has been previously validated by means of Cronbach's alpha 0.82 (Moghri et al, ). It also has been used in several studies in Iran (Moghri et al, ; Raeissi, Reisi, & Nasiripour, ). In the present study, Cronbach's alpha of the questionnaire was 0.83.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations conducted by different researchers have found similar results. 18,22,23 A study that applied the HSOPS to 26 hospitals in Iran 20 observed that there was better perception in the dimension of The "staffing" dimension needs improvement, which may be an effect caused by a situation of an insufficient number of professionals with heavy workloads. This imbalance increases the risk relating to the assistance provided.…”
Section: Discussionmentioning
confidence: 99%
“…The HSOPSC, developed in English [28] for use in American hospitals, has demonstrated excellent psychometric properties [27]. The instrument has been disseminated to other countries, in multiple languages [8,24,[30][31][32][33][34][35][36]; however, published studies generally neglect to report the instrument translation method and validation data. When provided, the information is either limited or poor quality such as reporting a simple post hoc psychometric analysis.…”
Section: Introductionmentioning
confidence: 99%